STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI PROFESIONAL GURU PADA SMA NEGERI 1 PEUKAN BADA KABUPATEN ACEH BESAR - Zulkifli Zulkifli (Jurnal Ilmiah Didaktika, 2014)
The strategy of the head master of the school really influence the teachers’ competence profesionalism that being conducted by guiding and giving opportunity to the teacher to improve their profession. The aim of this study is to know the strategy of head master in utilizing the teacher teaching methods, the strategy of head master in evaluating the success of the teachers, and to know the situation of the school head master in improving the professional competence of the teachers at the state senior high school 1 Peukan Bada Aceh Besar. The approach used in this study is qualitative with descriptive method. The techniques used in data collection were observations, interviews and documentations. The subjects of the research were the head master of the school, school curriculum division, administration chairman, chairman on the students’ affairs, and subject teachers of SMAN 1 Peukan Bada. The results of the study show that the head master strategies in improving the profesional ism competence namely: (1) The teachers learning mastery; (2) The use of teaching-learning methods by involving the teachers in training activities, scientific activities, seminars, workshops, scientific writing in action research, team teaching, inhousing MGMPs, motivate teachers to continue their education and supervision; (3) The strategy of the headmaster of the school in evaluation and class supervision sometimes conducted suddenly. The results of the evaluations are collected into a head master note and be conveyed at the meeting and MGMPs forum activities as a follow-up evaluation on what has been carried out; (4) The obstacles faced by the head master of the school in improving profesional ism competence among others are: the time restriction of school head master and teachers to carry out their primary tasks, low motivation of the students and teacher in the late of retirement to master information technology, put work hour to support the teacher certification, and putting hours of work to support teacher certification.